Analysis of centrifugal dewatering: consolidation behaviour with and without supernatant - Fukuyama, Ryo; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2013)

(untitled)
Centrifugal dewatering is one of the effective methods for solid-liquid separation. Although it is used in many industrial processes, the dewatering process is difficult to analyse because various factors influence the process. In most of the centrifugal dewatering cases, the solid-liquid interface appears as soon as the centrifugal dewatering begins. The details of the dewatering process are as follows: